Rancang bangun sistem pengaturan kelembaban tanah secara real time menggunakan mikrokontroler dan diakses di web - Irwan Agus Saputro; Jatmiko Endro Suseno; Catur Edi Widodo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
A research on telemetry or remote measurement, for the parameters of soil moisture and temperature of the object remains in the form of agricultural land. The measured parameters such as soil moisture values are obtained from soil moisture sensors. In addition added also parameter value air temperature obtained by measuring the air temperature. In order to measure the air suh used sensor DS18B20. Both of the devices are read and controlled by a microcontroller ATmega328 with the Arduino software. Recipients get the value of soil moisture humidity value from the sensor. Data such as soil moisture and temperature value of the air is sent to the microcontroller, then transmitted to the database server by using the Internet network GSM. The system will be automatically watering when the soil moisture values are below standard. The system is using web interface that allows users to monitor soil conditions without the need for special receiver station. The results of this study, the system can perform the measurement values of soil moisture and air temperature to the server and perform automatic watering. This reasearch used three medium, wherein each soil moisture rises up to 99% in the first and second medium, in the third medium soil moisture rises up to 97%. The increase in the value of soil moisture caused by the automatical watering is based on parameter moisture used.Keywords: Soil Moisture Sensor, Sensor DS18B20, telemetry by GSM internet, Arduino